Diabetic foot prevention: an integrative review / Prevenção do pé diabético: uma revisão integrativa - Kleviton Leandro Alves dos Santos; Tamiris de Souza Xavier; Raquel dos Santos Vieira Siqueira; Ana Paula Ramos da Silva Duarte; Andressa Ferreira Leite Ladislau (Universidade Estadual de Alagoas, 2019)
Diabetes Mellitus is a set of metabolic disorders, which has as its main characteristic hyperglycemia, being an epidemic that affects millions of people. Diabetes Mellitus is classified into two types. Type 1 is more common in children and adolescents, while type 2 affects adults with a family history of diabetes. Foot problems represent one of the most important chronic complications of diabetes. A series of anatomopathological and peripheral neurological changes causes the appearance of pressure points and skin dryness that compromise the feet of the diabetic patient. The nursing team has as its main role the orientation of patients and family members in care. The objective of this study was to identify the actions of the nurse in the care of patients with diabetic foot in order to present an accessible survey of the main aspects of diabetic ulcer prevention. This is an integrative review using online journals indexed in the portals of the Virtual Health Library, about nursing interventions for treatment (care) to the patient with diabetic foot. Discussion: All studies were classified with IV level of evidence and were derived from the Latin American and Caribbean Literature in Health Sciences database. Detailed physical examination was the most cited recommendation among the articles, followed by the use of shoes appropriate, the use of cotton socks, clean and white, moisturizing, nail cutting, proper nutrition and practice of physical activity. It is concluded that it is necessary to build scientific knowledge through health research, and this study indicates the need for a continuous search for new strategies for prevention and care of the feet.